1982
DOI: 10.2135/cropsci1982.0011183x002200050022x
|View full text |Cite
|
Sign up to set email alerts
|

Techniques of Screening Peas for Resistance to Phoma medicaginis var. pinodella1

Abstract: Footrot and foliar phases of the disease caused by Phoma medicaginis var. pinodella in peas (Pisum sativum L.) were studied. Major objectives were to develop repeatable inoculation procedures and to identify pea lines resistant to footrot and foliar infection. All tests were conducted under controlled environmental conditions. Fungal spore concentrations and plant age at inoculation were important for identifying differences in disease reactions among lines. Significant differences in reactions to footrot were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…We show that the best conditions to identify partial resistance are those with intermediate inoculum pressure, marginally favouring the pathogen. This idea was supported by Sakar et al (1982) who showed that intermediate concentrations of P. medicaginis var. pinodella inoculum gave a better separation of mean foot-rot disease scores for three cultivars, compared to low or high concentrations.…”
Section: Expression Of Partial Resistancementioning
confidence: 79%
“…We show that the best conditions to identify partial resistance are those with intermediate inoculum pressure, marginally favouring the pathogen. This idea was supported by Sakar et al (1982) who showed that intermediate concentrations of P. medicaginis var. pinodella inoculum gave a better separation of mean foot-rot disease scores for three cultivars, compared to low or high concentrations.…”
Section: Expression Of Partial Resistancementioning
confidence: 79%
“…In one experiment, where a larger number of plants was inoculated, inoculum was applied to seeds instead of directly to stems. To do this, seeds were surface-sterilised in sodium hypochlorite solution, washed in sterile water, as above, then immersed in a suspension of 106 spores m1-1 for 10 minutes (Sakar et al, 1982). After 14 days growth in compost (Fisons Universal) in a seed tray in a glasshouse at 15 ° C, each plant was assessed on a six-category scale (Table 2).…”
Section: Testing For Stem Resistancementioning
confidence: 99%
“…Screening for black spot resistance in field pea in Australia and elsewhere has largely focused on D. pinodes (6,18,23,35,50,52,53), much less so on P. pinodella (2,22,36), and not at all on P. koolunga. was the most virulent of the three pathogens in terms of stem disease, and its AUDPC MR was significantly higher than that of D. pinodes, previously considered the most important pathogen in the black spot complex (31,32).…”
Section: Discussionmentioning
confidence: 99%